Attitudes, perceptions and understanding amongst teenagers regarding teenage pregnancy, sexuality and contraception in Taung - T. Kanku; Bob Mash (South African Family Practice)
Background: South African teenage pregnancy rates remain high by international comparison and, in the rural town of Taung, the rate of 13% is twice the national average of 6.5%. Teenage pregnancy is a risk factor for disruption of education, future unemployment, sexually transmitted infections, HIV, preterm birth and poor mental health. The aim of this study was to understand the attitudes and perceptions of teenagers in Taung regarding teenage pregnancy and to explore their understanding of sexuality and contraception. This study intended to contribute to a deeper understanding by exploring teenagers’ own perceptions on the matter, to identify factors that, in their view, may influence the risk of pregnancy and suggest possible interventions. No previous studies from the Taung area have been identified.